The, A Peran Teknologi Keuangan dalam Meningkatkan Inklusi Keuangan di Indonesia: Perspektif Akuntansi Keuangan - Anggraini, Desy Ismah; Lily Indah Pratiwi; Kusuma, Pramandyah Fitah Kusuma (Jurnal Ilmiah Wahana Akuntansi, 2025)
This study aims to analyze the influence of crowdfunding and P2P lending, market aggregators, risk and investment management, and the cashless society on financial knowledge, financial behavior, and financial attitudes among MSMEs in Benowo District, Surabaya . The research employed a quantitative method using the PLS-SEM approach with SmartPLS software. Data were collected through questionnaires distributed to MSME actors and analyzed by testing validity, reliability, and the significance of the relationships among variables. The findings reveal that all hypotheses (H1–H12) were supported, with the key result showing that the use of crowdfunding and P2P lending has a significant impact on enhancing MSMEs’ financial knowledge, behavior, and attitudes. Furthermore, market aggregators were found to improve financial literacy while influencing financial behavior and attitudes. The risk and investment management variable also plays a crucial role in promoting more cautious and disciplined financial management in terms of knowledge, behavior, and attitudes. Meanwhile, the adoption of the cashless society significantly contributes to strengthening digital financial literacy, fostering more organized financial recording behavior, and shaping a more modern financial attitude among MSMEs. These findings contribute theoretically to the body of literature on fintech and financial literacy, while also offering practical implications for MSMEs, fintech service providers, and policymakers in designing more effective financial education programs and regulatory frameworks.